Strengthening the agricultural technology dissemination through Institutional partnership-based extension model - SHARMA, J P; SHARMA, AMBRISH KUMAR; DABAS, J P S; SHARMA, NISHI; DUBEY, SHANTANU KUMAR; AHMAD, NAFEES; KUMBHARE, N V; DUBEY, A V; KISHORE, NAND; SINGH, KISHAN; MAURYA, P P (The Indian Journal of Agricultural Sciences, 2020)
Partnership among institutions have been globally recognised as useful tool for effective extension for development of agriculture and rural dwellers. This have been proved through a national level public-private partnership-based technology dissemination extension model that was executed across 15 states of India categorized into six regions for the period from 2009-10 to 2015-16. There were 13 public institutions (9 SAUs and 4 ICAR institutes) and 41 voluntary organizations involved in this project with ICAR-IARI, New Delhi as the nucleus institution from where the multi-disciplinary integrated technology and packages were disseminated. The programme was monitored and evaluated through a well-structured inbuilt mechanism of annual review workshop, project area visits; monthly, six monthly and annual progress reporting and contingency field level workshop. During the period of six years, 21211 on-farm technology demonstrations were conducted which covered 6565 ha of area. About 30000 farmers across 15 selected states were directly and indirectly benefitted from different interventions of the project.The farmer level feedback helped to evolve two new varieties of paddy and participatory on-farm seed production ensured self-sufficiency by way of generating the quality seed pool for paddy (4526 q), wheat (7965 q) and vegetables (15 q). Based on the experiences, expected potential of the outcome have been implicated.